BOTULINUM TOXIN FOR TREATMENT OF CHRONIC ANAL FISSURE - Hamawandi, Nizar (Journal of Sulaimani Medical College, 2024)
Background Chronic anal fissure is a common disease that affects both sexes especially young adults. It causes pain and bleeding after defecation. Objectives The objective of the study was to determine whether injection of botulinum toxin into the internal anal sphincter to treat chronic anal fissures is safe and effective. patients and Methods A prospective study was conducted from April 1, 2018, to March 31, 2023, over a five-year period in a private surgical clinic in Sulaymaniyah, Iraq. Data were collected from 63 patients about presenting symptoms, physical examination, procedure and follow-up. A dose of 50 U of botulinum toxin were injected into either side of the fissure at three and nine o’clock. Re-epithelization of the anal fissure and total absence of pain defined complete healing of the fissure. A previously healed fissure that relapsed, had recurring symptoms, and was clinically detectable upon physical examination was referred to as a recurrence. Results At 2-months follow-up complete healing of the fissure was present in 46/63 patients (73.01%) after receiving one dose of botulinum toxin injection. At 12-months follow-up, complete healing of the fissure was present in 52/63 patients (82.53%) after receiving two injections of botulinum toxin injection. The recurrence rate was 9/63 patients (12.28%), anal incontinence rate for flatus was 1/63 patients (1.58%) that was mild, temporary, lasted for 3 weeks and disappeared spontaneously. Conclusion A safe, and effective method for treating chronic anal fissure is injection of botulinum toxin into the internal anal sphincter
Keywords: Chronic anal fissure Botulinum toxin